Addressing Burnout Amid Healthcare Workers: Creative Approaches For Stamina And Well-Being In Saudi Arabia (The Review of Diabetic Studies, 2024)
Burnout among medical professionals in Saudi Arabia is an increasing problem, primarily resulting from heavy workloads, emotional stress, and organizational shortcomings. Unaddressed burnout negatively impacts workers' health and job performance, ultimately diminishing the quality of patient care. This report assesses the causes and consequences of burnout among health care workers in Saudi Arabia and proposes approaches to improve stamina and well-being. Addressing burnout and supporting Vision 2030 objectives requires strengthening support systems, promoting the use of health resources, improving workflow management through technology, and promoting cooperation and acknowledgment within the workforce.